The Effect Of Educational Inequality On Economic Growth In Indonesia - Liyana, Nur Farida (Politeknik Keuangan Negara STAN, 2023)
Education is the elevator of the Indonesian economy. Where education is able to improve the welfare of society. However, the development of education in Indonesia is not evenly distributed. This inequality can be felt both between villages and cities as well as between regions in Indonesia. In theory, the occurrence of educational inequality will increase the poverty rate which will have an impact on decreasing economic growth. So in this study we want to examine the effect of educational inequality on economic growth by taking into account other variables, namely the poverty rate, population and government spending on education. The data used is secondary data from 34 provinces in Indonesia from 2015 to 2020 sourced from the Central Bureau of Statistics and the Directorate General of Fiscal Balance, Ministry of Finance. The results obtained are true that education inequality exists in Indonesia, even though the scale is still relatively low to medium. However, statistically it is found that educational inequality has a significant negative effect on economic growth. In contrast to the educational inequality, poverty rate, population and government spending on education have a positive effect, although not significant.